The Strategic Role of Mediators in Resolving Domestic Conflicts and Preventing Divorce - Rasyid Muzhar (Unram Law Review, 2025)
Marriage is for life, but reality is not always in line with expectations. Households will always be hit by problems, when a husband and wife are able to face them and find solutions, then the household will last. However, if the opposite happens, then the household will end. One of the causes of disputes in the household is due to violence. Violence in various forms in the household can come from the husband or wife or children, but women are often the victims. Therefore, mediation efforts by a mediator are very necessary as a mediator and peacemaker. Even though the mediator is not the only person who determines the success of mediation, the mediator's role in the mediation process is very determining. Mediators who act as mediators or judges must equip themselves with abilities that include basic skills and the ability to understand the character of the parties being mediated. Apart from ability, you must also have strong determination and sincerity which is manifested in seriousness to reconcile.